Whose History? Engaging History Students through Historical Fiction - Rodwell, Grant (University of Adelaide Press, 2013)
Whose History? aims to illustrate how historical novels and their related genres may be used as an engaging teacher/learning strategy for student teachers in pre-service teacher education courses. It does not argue all teaching of History curriculum in pre-service units should be based on the use of historical novels as a stimulus, nor does it argue for a particular percentage of the use of historical novels in such courses. It simply seeks to argue the case for this particular approach, leaving the extent of the use of historical novels used in History curriculum units to the professional expertise of the lecturers responsible for the units.